Pemberdayaan sosial-ekonomi masyarakat Desa Betao Riase melalui program KKN Etnografi: Studi kasus di Kecamatan Pitu Riawa - Mutiara Wulandari; Mardatillah; Surya Baskara Jaya; M. Adely Ihsan; Muhammad Rigan Yusri; Mentari Nur Arafah; Muh. Zulkifli; Rahmat; Eka Mawarni; M. Aldi Muhtadibillah; Bahruddin; Suherman (Jurnal Dedikasi Masyarakat, 2022)
The ethnographic Community Service Program (KKN) in Betao Riase Village, Pitu Riawa District, Sidenreng Rappang Regency, was designed to address the socio-economic challenges of rural communities that rely on agricultural products without added value. Through an ethnographic approach, the KKN team conducted participatory observations and in-depth interviews to understand the local social and cultural structures as a basis for intervention. During the 40-day implementation, the program focused on four main areas: education and religion, facilities and infrastructure, economy and industry, and social and community. The results of the program include improving students' literacy skills, participation in religious activities, production of durian jam as an MSME product, and training in liquid organic fertilizer to support sustainable agriculture. Cooperation activities and the celebration of the 76th Anniversary of the Republic of Indonesia also strengthened the social cohesion of the community. Evaluations showed an increase in household income of up to 28.6%, a decrease in waste volume of up to 40%, and high community participation. This article confirms that the ethnographic approach in KKN is able to encourage community independence through collaboration between academics and residents, and provide a basis for development policies based on local potential and ecological awareness.